Evaluation of Nd0.8−xSr0.2CaxCoO3−δ(x = 0, 0.05, 0.1, 0.15, 0.2) as a cathode material for intermediate-temperature solid oxide fuel cells. Issue 27 (13th June 2022) - Du, Xu; Li, Songbo; An, Shengli; Xue, Liangmei; Ni, Yang
Abstract : The increase in Ca for Nd0.8− x Sr0.2 Ca x CoO3− δ limits the electronic compensation capacity, resulting in a decrease in CTE. The Ca-doped material maintains good electrochemical properties under CTE reduction and thus can be used as an IT-SOFC cathode. Abstract : A series of Nd0.8− x Sr0.2 Ca x CoO3− δ ( x = 0, 0.05, 0.1, 0.15, 0.2) cathode materials was synthesized by sol–gel method. The effect of Ca doping amount on the structure was examined by scanning electron microscopy (SEM), X-ray diffraction (XRD), thermal expansion, and X-ray photoelectron spectroscopy (XPS). Electrochemical properties were evaluated for possible application in solid oxide fuel cell (SOFC) cathodes. Results showed that second phase NdCaCoO4+ δ is generated when the Ca doping amount is higher than 0.1. The increase in Ca limits the electronic compensation capacity of the material, resulting in a decrease in thermal expansion coefficient (TEC). With the increase of Ca content, the conductivity increases at first and then decreases, and the highest value of 443 S cm −1 is at x = 0.1 and T = 800 °C. Nd0.7 Sr0.2 Ca0.1 CoO3− δ exhibits the lowest area specific resistance of 0.0976 Ω cm 2 at 800 °C. The maximum power density of Nd0.7 Sr0.2 Ca0.1 CoO3− δ at 800 °C is 409.31 mW cm −2 . The Ca-doped material maintains good electrochemical properties under the coefficient of thermal expansion (CTE) reduction and thus can be used as an intermediate-temperature SOFC (IT-SOFC) cathode.